Effects of fluid ingestion on brain-derived neurotrophic factor and cognition during exercise in the heat - Roh, H.-T.; So, W. Y.; Cho, S.-Y.; Suh, S.-H. (Journal of Human Kinetics, 2017)
We investigated the effects of fluid ingestion during exercise in different environments on the serum brain-derived neurotrophic factor and cognition among athletes. Ten collegiate male athletes (soccer, n = 5; rugby, n = 5) were enrolled, and they completed running tests in the following four conditions (60 min each): 1) thermoneutral temperature at 18°C (group 18); 2) high ambient temperature at 32°C without fluid ingestion (group 32); 3) high ambient temperature at 32°C with water ingestion (group 32+W); and 4) high ambient temperature at 32°C with sports drink ingestion (group 32+S). Serum brain-derived neurotrophic factor levels significantly increased in group 18 immediately after exercise when compared with those at rest and were significantly higher than those in group 32 immediately and 60 min after exercise (p < 0.05). In the Stroop Color and Word Test, significantly increased Word, Color, and Color-Word scores were observed in group 18 immediately after exercise compared to those at rest (p < 0.05). However, the Color-Word score appeared to be significantly lower in group 32 immediately after exercise compared to the other groups (p < 0.05) and at 60 min post-exercise compared to group 18 (p < 0.05). We found that the exercise performed in a thermoneutral environment improved cognitive function, but the exercise performed in a hot environment did not. The differences according to the exercise environment would be largely affected by brain-derived neurotrophic factor, and fluid ingestion regardless of the type of drink (water or sports beverage) was assumed to have contributed to the improvement in cognitive function caused by exercising in a hot environment.